Using microsoft word - Zager, Masha; Chase, Claire (Carmel, Indiana : Que Corp., 1987)
This is a guide on the use of Microsoft Word published in 1987. It covers major topics like The Basic Word; Words Useful Tools; and New Word Version 4 features.
Includes index.
II 15/01/2019
Loans
Keywords: Word processing